Um estudo sobre a adoção de soluções de internet das coisas por produtores de leite de Minas Gerais para superar seus principais desafios de produtividade - Sérgio Luiz Meyer Portugal (2019)
The objective of this work was to study the level of adoption of Internet of Things solutions by milk producers of Minas Gerais to solve, at least in part, their challenges to increase milk productivity. The justification for the study to be carried out comes from the socioeconomic importance of dairy cattle to the state of Minas Gerais and the ability of the Internet of Things solutions to help increase the productivity of the sector that has challenges in this regard. Through a descriptive and quantitative research, 199 milk producers from Minas Gerais were surveyed by the Balde Cheio Project. In all, 128 questionnaires were completed in 2017, with questions based on the theoretical framework that approached the Internet of Things and its diffusion as technology in Brazil and in the world, the productivity challenges of dairy farming in Brazil and the theoretical foundations of livestock precision milk. The results of the research were interpreted based on the validation of the hypotheses using structured, statistical data, with analysis of a large number of representative cases, recommending a final course of action, according to Mattar (2001) guidelines. There was a very low level of adoption of Internet of Things solutions by milk producers in Minas Gerais to support the increase in productivity. Almost all of the milk producers surveyed responded by not using Internet of Things solutions on their rural property. Most of them did not even know the expression "Internet of Things". On the other hand, from the moment they understood and agreed to the definition of IoT presented in the questionnaire, almost all the milk producers indicated an interest in receiving more information on the subject. It was concluded that there is a lack of knowledge among milk producers in Minas Gerais regarding the potential application of Internet of Things solutions to help improve the management of rural property and, consequently, increase their productivity. On the one hand, this issue is worrying, given the speed with which new technologies have appeared in the market, on the other, it is evident the opportunity for rural extension entities and suppliers of Internet of Things solutions applied to dairy farming to act together with producers.